Floppy's phonics book 24 - Hunt, Roderick (china, Oxford university press, 2011)
Level 4 Floppy's Phonics Sounds and Letters books revise the sounds introduced in Levels 1+ to 3 and introduce some alternative spellings for some of the sounds already learned. The sounds and alternative spelling are introduced in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.